2017
DOI: 10.1038/s41598-017-04328-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome changes between compatible and incompatible graft combination of Litchi chinensis by digital gene expression profile

Abstract: Plant grafting has been practiced widely in horticulture and proved as a useful tool in science. However, the mechanisms of graft healing or graft incompatibility remain poorly understood. In this study, Litchi chinensis cv. ‘Jingganghongnuo’ homograft (‘J/J’) and ‘Jingganghongnuo’/‘zhuangyuanhong’ heterograft (‘J/Z’) as compatible and incompatible combination, respectively, was used to study transcriptional changes between incompatible and compatible graft during graft union formation. Anatomical observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…Members of the PM ATPase gene family were up‐regulated at the graft interface of litchi ( Litchi chinensis ) for compatible grafts at 14 and 21 day after grafting (Chen et al . ). The PM ATPase genes were also up‐regulated at the graft union of grapevine heterograft 14 day after grafting (Cookson et al .…”
Section: Discussionmentioning
confidence: 97%
“…Members of the PM ATPase gene family were up‐regulated at the graft interface of litchi ( Litchi chinensis ) for compatible grafts at 14 and 21 day after grafting (Chen et al . ). The PM ATPase genes were also up‐regulated at the graft union of grapevine heterograft 14 day after grafting (Cookson et al .…”
Section: Discussionmentioning
confidence: 97%
“…Using this system, we first showed that exogenous treatment with cellulases promotes graft adhesion. Given that numerous candidate genes related to grafting have been identified through recent transcriptome analyses (Cookson et al 2014;Liu et al 2015;Melnyk et al 2015;Li et al 2016;Chen et al 2017;Wang et al 2019;Xie et al 2019;Kurotani et al 2020;Notaguchi et al 2020 Figure 3C). In both cases, no correlation was observed between adhesive force and graft area.…”
Section: Effect Of Cellulases On the Adhesion Of Nb Ivgmentioning
confidence: 99%
“…In regard to molecular mechanisms, studies have revealed the activity of enzymes, such as peroxidase and catalase, during grafting (Fernández-garcía et al 2004;Pina and Errea 2008;Irisarri et al 2015). Molecular genetic studies of grafting have been conducted in fruit trees, vegetables, and model plants (Cookson et al 2014;Wang et al 2014;Liu et al 2015;Melnyk et al 2015;Irisarri et al 2015;Li et al 2016;Matsuoka et al 2016;Chen et al 2017;Melnyk et al 2016;Matsuoka et al 2018;Wang et al 2019;Xie et al 2019;Kurotani et al 2020;Notaguchi et al 2020). Among the various findings, these studies have clearly shown that grafting is promoted by auxin action through the expression of genes related to auxin signaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only phytohormone action, many of the genes related to metabolism, the oxidative stress response, transport, and defense are involved in graft healing process. Transcriptomic analyses conducted on the grafts of fruit trees (Chen et al , 2017; Assunção et al , 2019) and the seedling grafts of Arabidopsis (Melnyk et al , 2018) and tomato (Wang et al ., 2019; Xie et al , 2019) identified that graft incision induced drastic transcriptomic changes including upregulation of the wound response genes after grafting.…”
Section: Introductionmentioning
confidence: 99%